Genome Assembly and Evolutionary Analysis of the Mandarin Duck Aix galericulata Reveal Strong Genome Conservation among Ducks. (30th May 2022) - Ng, Chen Siang; Lai, Cheng-Kuo; Ke, Huei-Mien; Lee, Hsin-Han; Chen, Chih-Feng; Tang, Pin-Chi; Cheng, Hsu-Chen; Lu, Meiyeh J.; Li, Wen-Hsiung; Tsai, Isheng Jason
Abstract: The mandarin duck, Aix galericulata, is popular in East Asian cultures and displays exaggerated sexual dimorphism, especially in feather traits during breeding seasons. We generated and annotated the first mandarin duck de novo assembly, which was 1.08 Gb in size and encoded 16, 615 proteins. Using a phylogenomic approach calibrated with fossils and molecular divergences, we inferred that the last common ancestor of ducks occurred 13.3–26.7 Ma. The majority of the mandarin duck genome repetitive sequences belonged to the chicken repeat 1 (CR1) retroposon CR1-J2_Pass, which underwent a duck lineage-specific burst. Synteny analyses among ducks revealed infrequent chromosomal rearrangements in which breaks were enriched in LINE retrotransposons and DNA transposons. The calculation of the d N / d S ratio revealed that the majority of duck genes were under strong purifying selection. The expanded gene families in the mandarin duck are primarily involved in olfactory perception as well as the development and morphogenesis of feather and branching structures. This new reference genome will improve our understanding of the morphological and physiological characteristics of ducks and provide a valuable resource for functional genomics studies to investigate the feather traits of the mandarin duck.